Breastfeeding experiences among employed mothers - Susanha Yimyam (2018)
Modernization and urbanization are often cited as threats to breastfeeding because ofchanging lifestyles and desires. Currently, most breastfeeding mothers who resume fulltimeemployment outside the home face difficulties with breastfeeding, especially inworkplaces without a support program. Conflicts between women's productive andreproductive roles are intensified by rapid development and social change. Combining theconflicting rights and demands of these roles poses an increasing challenge to healthpolicy formulation and health care services as well as family and workplace support.This chapter reviews the global literature to identify situations and experiences ofbreastfeeding among employed mothers. The chapter focuses on the impact on full-timeemployed mothers. It discusses the context and difficulties of combining breastfeedingwith employment and the dilemma of conflict between reproductive and productivedemands. The obstacles mothers faced in their efforts to maintain lactation whilesimultaneously undertaking paid work. The resulting stresses and conflicts affected boththeir physical and emotional health. Some women reported guilt and many reporteddecreased self-care and poor eating due to exhaustion.In conclusion, having supportive employers, adequate paid maternity leave, flexiblework hours, and child care facilities at the place of work as well as practical support fromhusbands with domestic work can enhance the successful integration of breastfeeding andemployment. Women should not have to choose between their maternal and productiveroles. It is imperative that multisectoral strategies be developed so that employedwomen-among the world's most enthusiastic breastfeeders-can undertake paidemployment and continue to give their infants the best start in life. © 2013 Nova Science Publishers, Inc. All rights reserved.